Household coping and recovery from nature's wrath: Rising from the ruins of Yolanda - Majah-Leah V. Ravago; Dennis S. Mapa (University of the Philippines, School of Economics (UPSE), 2015)
Typhoon Yolanda (Haiyan), one of the strongest storms ever recorded, hurled massive destruction across the central part of the Philippines in Nov 2013. The question foremost in everybody's mind is whether the Yolanda-affected families have already recovered. Using the PCED Social Protection Survey conducted 6 months after the disaster, we find that 36% of the households have yet to experience even partial recovery. We investigate the various coping mechanisms that the Yolanda-affected families have employed to aid in their recovery using logit-regression analysis. We find that the most prominent coping activity is taking precautionary measures and asset disposal. Government assistance positively aided in the recovery but only of the poor. Further, the probability of recovery is lower for those that are located in the badly-hit Leyte relative to the other provinces.
Keywords: Q54; D81; I38; 330; Natural Disaster; shock; coping